Relationship of family role with elderly quality of life in Posyandu Cendrawasih Pasir Tuntung Village, Kotapinang District, South Labuhanbatu Regency in 2020 - Zuidah Zuidah (Science Midwifery, 2020)
Elderly is someone aged 60 years and over with the elderly being divided into three categories, namely 45-59 years, 60-69 years old, and 70 years old, while quality of life is a functional condition of the elderly which includes physical conditions, namely activities carried out daily, dependence on medical assistance and the role of a much needed family. The problem is the declining quality of life of the elderly and this occurs because the family does not pay attention to the elderly, especially in the health sector. The research objective was to determine the relationship between the role of the family and the quality of life of the elderly in the Cendrawasih Elderly Posyandu, Pasir Tuntung Village, Kotapinang District, Labuhanbatu Selatan Regency in 2019. The research design was cross sectional which emphasized the time measurement and data observation between the dependent and independent variables. The sampling technique in the study this is to use accidental sampling. The study sample was 29 people who had been selected by chance (NRS). Data analysis used chi-square test. The results of the study, the relationship between the role of the family and the quality of life of the elderly at Cendrawasih Elderly Posyandu, Pasir Tuntung Village, Kotapinang District, Labuhanbatu Selatan Regency, the majority of the family's role is quite 13 people (44.8% and the majority of the elderly's quality of life is good 14 people (48.2) obtained p-value = 0.707> α = 0.05 which means there is no relationship between family roles and the quality of life of the elderly. The conclusion of this study is that there is no relationship between family roles and the quality of life of the elderly. Kecamatan Kota Pinang, Kabupaten Labuhanbatu Selatan can routinely provide counseling about the elderly so that the quality of the elderly is better.